36th Annual Hawaii International Conference on System Sciences, 2003. Proceedings of The 2003
DOI: 10.1109/hicss.2003.1174359
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational culture in the management of clinical e-health systems

Abstract: The research here presented focuses upon the informal, social, and cultural side of managerial coordination and control as manifested in clinical e-health systems. Specifically, the research seeks to analyze and determine the role specific dimensions of organizational culture may have upon effective managerial coordination and control in clinical e-health systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…Tanriverdi and Iacono, 1998;Dwivedi et al 2001), people and organizational issues (e.g. Lorenzi et al, 1997;Aarts et al 1998;Berg, 2001), social communication patterns (Davidson, 2000), organizational structure and culture (Bangert and Doktor, 2003), and enactments of different structures of reference by different stakeholder groups (Constantinides and Barrett, 2006). These studies point to the importance of organizational processes in explaining the success and failure of telehealth innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Tanriverdi and Iacono, 1998;Dwivedi et al 2001), people and organizational issues (e.g. Lorenzi et al, 1997;Aarts et al 1998;Berg, 2001), social communication patterns (Davidson, 2000), organizational structure and culture (Bangert and Doktor, 2003), and enactments of different structures of reference by different stakeholder groups (Constantinides and Barrett, 2006). These studies point to the importance of organizational processes in explaining the success and failure of telehealth innovations.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Bangert, Doktor [21], Yellowlees [22] and the present study all showed that the structure of human resources has a positive and significant role in the success of a telemedicine system. Despite the fact that one of the management challenges in changing health service provision models or introducing a new model is the resistance of staff to changes.…”
Section: Discussionmentioning
confidence: 90%
“…Telehealth innovations have great potential to enhance accessibility to healthcare, reduce cost of care, and enhance quality of care ( Bangert and Doktor 2003;Institute of Medicine 1996;Office of Technology Assessment 1995). Despite such potential, many telehealth innovations are either not accepted or not successfully implemented (Bangert and Doktor 2003;Institute of Medicine 1996) due to poor technology performance, organizational issues, and legal barriers (Bashshur 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Despite such potential, many telehealth innovations are either not accepted or not successfully implemented (Bangert and Doktor 2003;Institute of Medicine 1996) due to poor technology performance, organizational issues, and legal barriers (Bashshur 2000). It is also widely acknowledged that physicians and other medical staff are notorious for their nonresponsiveness to and resistance to use of information technologies (Anderson 1997;Lapointe and Rivard 2005).…”
Section: Introductionmentioning
confidence: 99%